2019
DOI: 10.3390/w11050922
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Environmental and Anthropogenic Factors on Microbial Ecology and Sanitary Threat in the Final Stretch of the Brda River

Abstract: Ecology of aquatic microorganisms depends on a number of environmental parameters. The additional influence of anthropogenic factors is connected with sanitary risk, particularly in urban areas. The study was aimed at assessing the impact of physicochemical and biological parameters on the abundance and activity of bacterioplankton under different spatio-temporal conditions in the urbanized section of the Brda River. The evaluation of sanitary pollution of water was accompanied by the assessment of antibiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The lack of a significant temporal trend in the higher density septic watersheds may suggest that spatial differences in septic system density exhibit a stronger influence on river FIB communities than temporal fluctuations. Past studies also found that spatial variability affected river bacterioplankton communities more than seasonal variation [39][40][41][42][43]. FIB communities may be affected by, but not limited to, changes in salinity [40], reduced river flow and sedimentation rates [42], and land use [24,40,41,43].…”
Section: Septic System Densitymentioning
confidence: 96%
“…The lack of a significant temporal trend in the higher density septic watersheds may suggest that spatial differences in septic system density exhibit a stronger influence on river FIB communities than temporal fluctuations. Past studies also found that spatial variability affected river bacterioplankton communities more than seasonal variation [39][40][41][42][43]. FIB communities may be affected by, but not limited to, changes in salinity [40], reduced river flow and sedimentation rates [42], and land use [24,40,41,43].…”
Section: Septic System Densitymentioning
confidence: 96%